2021
DOI: 10.1021/acs.jpcc.1c05126
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Particle Spectroscopy with One-Stage Lock-In Implementation for Magnetic Bioassays with Improved Sensitivities

Abstract: In recent years, magnetic particle spectroscopy (MPS) has become a highly sensitive and versatile sensing technique for quantitative bioassays. It relies on the dynamic magnetic responses of magnetic nanoparticles (MNPs) for the detection of target analytes in the liquid phase. There are many research studies reporting the application of MPS for detecting a variety of analytes including viruses, toxins, nucleic acids, and so forth. Herein, we report a modified version of the MPS platform with the addition of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…However, upon the addition of target analytes, the MNPs undergo clustering events, thus restricting Brownian relaxation, which leads to a drop in the harmonic amplitude. Two important factors help improve the sensitivity of a volumetric bioassay MPS system: (1) Brownian dominant behavior of MNPs, what it means to our context is that a larger % drop (Δ) from the unbound state (simultaneous Brownian and Néel relaxation possible) to the bound state (only Néel relaxation possible) benefits sensitivity; and (2) higher harmonic amplitude from unbound MNPs, this has an indirect effect on sensitivity as it allows for the use of smaller quantities of MNPs for bioassay testing, which has proven to improve the sensitivity significantly. , Because of this unique dependence, instead of giving general guidelines, we will limit ourselves to only a few categorical reviews that can help improve sensitivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, upon the addition of target analytes, the MNPs undergo clustering events, thus restricting Brownian relaxation, which leads to a drop in the harmonic amplitude. Two important factors help improve the sensitivity of a volumetric bioassay MPS system: (1) Brownian dominant behavior of MNPs, what it means to our context is that a larger % drop (Δ) from the unbound state (simultaneous Brownian and Néel relaxation possible) to the bound state (only Néel relaxation possible) benefits sensitivity; and (2) higher harmonic amplitude from unbound MNPs, this has an indirect effect on sensitivity as it allows for the use of smaller quantities of MNPs for bioassay testing, which has proven to improve the sensitivity significantly. , Because of this unique dependence, instead of giving general guidelines, we will limit ourselves to only a few categorical reviews that can help improve sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, single-core MNPs present with a larger harmonic drop, meaning that the Brownian relaxation mechanism is more dominant for these nanoparticles; on the other hand, they also offer a smaller harmonic amplitude. This means that a smaller number of multicore MNPs can be utilized instead for the generation of a suitable harmonic amplitude for bioassay applications, which has been shown to provide significant sensitivity improvements. , Due to this dichotomy between the harmonic amplitude strength and corresponding Δ, the choice between single- or multicore MNPs for better sensitivity has been left for further in-depth investigation.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This feasibility attempt allows us to explore inexpensive bioassays on our MPS platform for future high-volume tests at the users’ ends and in regions with scarce medical resources. Furthermore, it is reported that for MPS-based homogeneous bioassays, lower MNP concentrations could improve the detection sensitivities of biomolecules. , …”
Section: Materials and Methodsmentioning
confidence: 99%
“…In this work, we immobilized MNP chains of varying concentrations and alignments of easy axes relative to the probing magnetic field directions. The static and dynamic magnetization responses of these MNP chain samples are characterized by a standard VSM and a home-built magnetic particle spectroscopy (MPS) system, , respectively. MPS is a 1D magnetic particle imaging (MPI) platform, and it has been reported for magnetic biosensing applications that utilize the dynamic magnetization responses of MNPs as well as for examining the suitability of MNP tracers for MPI imaging.…”
Section: Introductionmentioning
confidence: 99%